Chemical Standardization of Extracts of CalophyllumBrasiliense with Antiplasmodial and Cytotoxic Activity (2019)
Malaria is considered one of the health problems in many parts of the world. The objective of this work is to implement standardized extraction strategies using analytical methodologies of the Calophyllum brasiliense Cambess. for the validation of antiplasmodial potential in vitro. Using HPLC chromatographic and chemical characterization techniques (13C-NMR, 1H-NMR), the marker substance was identified and quantified on continuous cultures of Plasmodium falciparum chloroquine-sensitive strain NF-54 and cytotoxicity in cell lines U-937 and HepG2used the antimalarial potential of the C. brasiliense. The best extracts were stems with ethyl acetate and extraction after 4 hours, presented a yield of 4.154±0.301%, a promising antiplasmodial activity of IC50 = 9.013 } 1.288 μg/mL, a cytotoxicity of CC50HepG2 =43.340±3.159 μg/mL, an IS = 4.808 and a content of marker substancesnamedsoulatrolide (1)of C1 =0.257±0.021%. A new analytical method for the quantification of marker substances was established and the best extracts were obtained. The extracts presented promising pharmacological activities for studies that guarantee reproducibility and effectiveness in biological tests in vivo and framed in the transformation of a phytotherapeutic product.